Pelaksanaan Perjanjian Pinjam Meminjam dengan Jasa Koperasi yang Belum Berbadan Hukum di Desa Nobo Kabupaten Flores Timur - Marselina Bali Ola Nama Tukan; Yossie Maria Yulianty Jacob; Husni Kusuma Dinata (Pusat Riset dan Inovasi Nasional, 2025)
The execution of a loan agreement is a form of binding engagement between the lender and the borrower. This agreement must fulfill the validity requirements as stipulated in Article 1320 of the Indonesian Civil Code. In practice, there are still cooperatives that operate without legal entity status but continue to provide lending services, such as Pringkop Cooperative in Nobo Village, Ile Boleng District, East Flores Regency. This study aims to examine the implementation of loan agreements facilitated by Pringkop Cooperative, which operates without legal entity status, as well as the factors influencing the community's decision to engage in such agreements. This research employs empirical approach, utilizing primary and secondary legal materials. The analysis method applied is qualitative descriptive analysis. The findings of this study indicate that: (1) The execution of loan agreements in Pringkop Cooperative is conducted in a simple manner, without notarized deeds or legally valid written agreements, posing risks to both parties in terms of dispute resolution. Nevertheless, the cooperative continues to operate based on a trust system and an orally agreed-upon repayment mechanism. (2) The factors influencing the community to engage in loan agreements with Pringkop Cooperative include ease of access, trust in the cooperative, and the economic conditions of the community, which require quick loans without complex procedures. Additionally, social and cultural factors contribute to the sustainability of this practice, as family relationships and local customs play a significant role in loan transactions.